Giant-cell arteritis related strokes: scoping review of mechanisms and rethinking treatment strategy? - Bonnan, Mickael; Debeugny, Stephane (Frontiers in Neurology, 2023)
Stroke is a rare and severe complication of giant cell arteritis (GCA). Although early diagnosis and treatment initiation are essential, the mechanism of stroke is often related to vasculitis complicated by arterial stenosis and occlusion. Its recurrence is often attributed to early steroid resistance or late GCA relapse, so immunosuppressive treatment is often reinforced. However, many questions concerning the mechanisms of stroke remain elusive, and no review to date has examined the whole data set concerning GCA-related stroke. We therefore undertook this scoping review. GCA-related stroke does not necessarily display general signs and inflammatory parameters are sometimes normal, so clinicians should observe caution. Ischemic lesions often show patterns predating watershed areas and are associated with stenosis or thrombosis of the respective arteries, which are often bilateral. Lesions predominate in the siphon in the internal carotid arteries, whereas all the vertebral arteries may be involved with a predominance in the V3-V4 segments. Ultrasonography of the cervical arteries may reveal edema of the intima (halo sign), which is highly sensitive and specific of GCA, and precedes stenosis. The brain arteries are spared although very proximal arteritis may rarely occur, if the patient has microstructural anatomical variants. Temporal artery biopsy reveals the combination of mechanisms leading to slit-like stenosis, which involves granulomatous inflammation and intimal hyperplasia. The lumen is sometimes occluded by thrombi (<15%), suggesting that embolic lesions may also occur, although imaging studies have not provided strong evidence for this. Moreover, persistence of intimal hyperplasia might explain persisting arterial stenosis, which may account for delayed stroke occurring in watershed areas. Other possible mechanisms of stroke are also discussed. Overall, GCA-related stroke mainly involves hemodynamic mechanisms. Besides early diagnosis and treatment initiation, future studies could seek to establish specific preventive or curative treatments using angioplasty or targeting intimal proliferation.